Optimization and Application of Unsaturated Soil Thermal Conductivity Model - Wang Zhihua; Wang Tian; Wang Fenghao (Zhileng xuebao)
Based on the models of Campbell and de V-1, a new mathematic model for predicting soil thermal conductivity is developed in this paper. Using the parameters shape factors ( ) and soil solid thermal conductivity ( ), the Campbell model is calculated by the method of the de V-1 model. According to this method, the soil solid thermal conductivity and shape factors are considered to be soil solid components, and include the effect of temperature on the soil solid thermal conductivity. By comparing the Campbell and de V-1 models, the measured results are in good accordance with the numerical ones, and the model shows better performance when predicting soil thermal conductivity. In addition, the effects of soil temperature and moisture on different soil thermal conductivities are studied. The results indicate that under the same soil temperature and moisture, the thermal conductivity of sand is greater than that of loam, and the thermal conductivity of loam is greater than that of clay. This will provide new ideas for establishing a coupled heat and moisture transfer model in unsaturated soil for heat exchangers.